2018
DOI: 10.1186/s40645-017-0159-0
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of the large-scale atmospheric state driving downscaling: a perspective on dynamical downscaling for regional climate study

Abstract: In this study, we provide a perspective on dynamical downscaling that includes a comprehensive view of multiple downscaling methods and a strategy for achieving better assessment of future regional climates. A regional climate simulation is generally driven by a large-scale atmospheric state obtained by a global climate simulation. We conceptualize the large-scale state based on reconstruction by combining decomposed components of the states, such as climatology and perturbation, in different global simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…The number of TCs approaching Japan is projected to reduce, whereas the TC precipitation rate increases under the future climate. This is consistent with the projection by AGCM20 (Lui et al 2018) and the projections using dynamical downscaling (Knutson et al 2015;Huang et al 2016;Nishizawa et al 2018). The frequency of moderate TC precipitation, which sometimes occurs under the present climate, does not change significantly because of the cancelation of these two contrary effects.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The number of TCs approaching Japan is projected to reduce, whereas the TC precipitation rate increases under the future climate. This is consistent with the projection by AGCM20 (Lui et al 2018) and the projections using dynamical downscaling (Knutson et al 2015;Huang et al 2016;Nishizawa et al 2018). The frequency of moderate TC precipitation, which sometimes occurs under the present climate, does not change significantly because of the cancelation of these two contrary effects.…”
Section: Discussionsupporting
confidence: 89%
“…The changes in the total TC precipitation and the frequency distribution depend on the balance between two competing factors: reduction in TC number and intensification of TC precipitation rate. In Nishizawa et al (2018), in which dynamical downscaling data for the projection by AGCM20 with C0 SST distribution was used, the reduction of TC number surpasses the intensification of precipitation, and a reduction of total TC precipitation are projected, which is consistent with our result for C0 SST. Using the projection by AGCM20 that is used for the boundary condition of NHRCM05, Kitoh and Endo (2016) showed that the annual maximum daily precipitation associated with TCs will decrease in the future owing to a reduction in TC number.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These large‐scale climate states are shown as diamonds on the climatology–perturbation phase space in Figure a, according to A2017 and Nishizawa et al . (), and they are used as RCM boundary conditions in our analysis. The vertical axis indicates the changes in a regional climate target variable that are estimated from downscaling experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Nishizawa et al () proposed the interpretation of the downscaling procedure using a conceptual phase‐space diagram for the climatology and perturbation components. According to the proposal, a constraint to an RCM can be established by combining two components from different data sets.…”
Section: Conceptual Idea and Mathematical Descriptionmentioning
confidence: 99%